THE SYSTEM PTS-PDS-NIS BETWEEN 1200° AND 700°C - Verryn S.M.C.; Merkle R.K.W. (My University, 2002)
Results of experimental investigations in the dry system PtS-PdS-NiS between 1200° and 700°C are presented. The phases encountered in the experimental runs are synthetic cooperite (( Pt,Pd,Ni)S), synthetic braggite (( Pt,Pd,Ni)S), synthetic vysotskite ((Pd,Pt,Ni)S), quenched sulfide liquid, and Ni 1-xS. Synthetic cooperite is stable to temperatures above 1200°C, whereas synthetic braggite is stable at temperatures below 1100°C, and synthetic vysotskite, below 1000°C. Below 900°C in the system PtS-PdS- NiS, Ni-saturated synthetic cooperite, braggite, and vysotskite coexist with Ni 1-xS. At 900°C, only Ni-saturated, Pd-free synthetic cooperite coexists with Ni 1-xS, and synthetic braggite and Pd-bearing synthetic cooperite coexist with a Pd-Ni-Pt sulfide melt. At temperatures ≥ 1000°C, Ni-saturated synthetic cooperite and braggite coexist with a Pd-Ni-Pt sulfide melt. In the experiments, there is a clearly defined miscibility-gap between cooperite and braggite, but no gap was observed between braggite and vysotsk ite. The Ni content of braggite and vysotskite with varying Pt:Pd ratio in a Ni-saturated environment is a function of temperature. A higher Ni content indicates a lower temperature of equilibration, and can be estimated using the following equation: T ( °C) = 998.07 (±7.88) + 0.05 (±0.02) * Pt2 - 4.24 (±0.16) * Ni2. In cooperite, a similar relationship between the Ni content and the temperature of equilibration is applicable between 1200° and 900°C.
Keywords: system Pt–Pd–Ni–S; phase relations; experimental investigation; cooperite; braggite; vysotskite